Factors that influencing employee engagement among group risk department Malayan Banking Berhad / Farra Nadia Razali - Razali, Farra Nadia (Faculty of Business and Management, 2019)
Due to fast growing in business industry forced many company continuously adapting to changes in order to fit the differences need of workforce. Hence employee engagement has been one of the crucial issue faced by employer in this country. The reason is when there is high involvement of employee towards their job, it will lead to produce excellent performance in their job. Therefore, Employee engagement is key for the success of a business growth and productivity. Furthermore, the purpose of this research is to investigate the factor that influencing employee engagement at Group Risk, Malayan Banking Berhad. This study used convenience sampling techniques and online questionnaire as an instrument to collect data. The data from 72% out of 130 employees are collected then evaluated by using statistical package for the Social Science (SPSS) version 23 software. The result from Multiple Regression analysis indicates that all the elements in predict employee engagement which is work environment, leadership and team and co-worker relationship have positive and significant relationship with employee engagement. Moreover, work environment found to be the most influential variables towards employee engagement at Group Risk Malayan Banking Berhad.